Low-Power Agriculture IoT System with LoRa: Open Field Storage Observation - Kökten, Esma; Çalışkan, Bahadır Can; Karamzadeh, Saeid; Soyak, Ece Gelal (Electrical, Control and Communication Engineering, 2020)
The last decade has seen multiple research work on the use of LoRaWAN technology in smart agriculture. In open field storage, monitoring is crucial for increasing the logistics efficiency and improving crop quality. As battery maintenance is expensive in such areas, LoRa is a suitable technology that allows for low-power communications. Within the framework of the research, a prototype has been built for tracking goods in open field storage. The battery lifetime has been analysed through calculations and measurements using LoRa communications. Our findings indicate that although sleeping current has the smallest percentage, it has the greatest effect on increasing the battery life, for longer battery life LoRa node must have a low self-discharge battery, and finally, sensors are the main battery depleting factor on the LoRa node.